Electrochemical Detection and Characterization at Liquid/Liquid micro-Interfaces - Islam, Gazi Jahirul (Curtin University, 2021)
The purpose of this research is to investigate the electrochemical detection and characterization of different substances at liquid/liquid micro-interfaces which were created at the tips of the glass micropipettes. In this way, per- and polyfluoroalkyl substances (PFAS), PAMAM dendrimers and sulphate ions were investigated by voltammetric analysis. The successful detection of all substances provides the basis for improved analytical processes and various electrochemical properties were analysed to elucidate their transfer mechanisms at the interfaces.